Frost resistance and mechanical degradation characteristics of cement-stabilized macadam under the long-term freezing–thawing cycles. (12th September 2022) - Jie, Shaolong; Yue, Zurun; Sun, Zhiqi; Zhang, Hanbing; Hu, Tianfei; Sun, Tiecheng; Yuan, Lanlan; Xie, Peng; Mao, Shuai
Highlights: Three different cement contents and removal of two different fine particle sizes of cement-stabilized macadam (CSM) were tested. The mechanical strength characteristics were degraded by long-term freezing−thawing cycles. The removal size of larger fine particles had adverse effects on the strength and degradation rate of CSM. The increase in the cement content led to an increase in the frost resistance and strain energy density of CSM. The initial elastic modulus determined using unconfined compressive strength tests could be applied to characterize the stiffness of CSM for high-speed railway lines. Abstract: The high-speed railway subgrade in seasonal frozen soil regions should be able to resist long-term freezing and thawing cycles. In consideration of cement-stabilized macadam (CSM) as the subgrade surface material needs to have resistant to freeze–thaw strength deterioration. This study aimed to evaluate the mechanical degradation characteristics of CSM under the long-term freezing-thawing cycles by the unconfined compressive strength tests. Three different cement contents (3 %, 5 %, and 7 %) and removal of two different fine particle sizes (0.1 and 0.25 mm) of CSM were studied and analyzed. The number of freezing–thawing cycles was set to 0, 1, 3, 5, 7, 10, 15, 20, 30, 40, and 50, respectively. Based on the unified calculation model of strength deterioration, evaluation index of frost resistance, and analysis of strain energy density failure, C5 P0.1 could be used in seasonal frozen soil regions. If the subgrade bed had requirements for permeability, fine particles with larger sizes could be removed. The results indicated that, first, the strength of fine particles with larger size removal was smaller and the strength deterioration was faster under the same cement content. Second, when the cement content was higher, CSM showed better resistance to freezing–thawing strength degradation. Further, when the cement content increased, the increase in the amplitude of strain energy density varied significantly; the increasing effect was the best when the cement content increased from 3 % to 5 %. Finally, the initial elastic modulus of the Duncan-Chang hyperbolic model was used to characterize the stiffness of CSM in the high-speed railway subgrade bed. This study revealed the mechanical degradation characteristics of CSM under the long-term freezing–thawing cycles with different cement contents and removal sizes of fine particles. The findings were useful for understanding the mechanical behavior of CSM under the long-term freezing–thawing cycles.